An investigation on diffusivity while achieving a cylindrical aluminide coating on metals using simultaneous spark plasma sintering of powders. (September 2019) - Chawake, Niraj; Ghosh, Pradipta; Eckert, Jürgen; Kottada, Ravi Sankar
Abstract: Simultaneous spark plasma sintering (SPS) of metal powders (Fe and Ni) with their respective aluminide powders (FeAl and NiAl) was attempted to produce a cylindrical aluminide coating on a cylindrical metal core. The interdiffusion zone (IDZ) formed between the metal and the aluminide was analyzed to evaluate the diffusion coefficient. The composition variation and the actual temperature estimated at the interface were taken into consideration while evaluating the diffusion coefficient. The diffusion coefficients estimated based on the IDZ are found to be higher than those obtained by conventional methods but are in agreement with those obtained from previous SPS studies. Graphical abstract: Unlabelled Image